ASUHAN KEBIDANAN PADA REMAJA NN P PENGKONSUMSIAN TELUR TERHADAP PENDERITA ANEMIA PADA REMAJA PUTRI DI PUSKESMAS TG BALAI KARIMUN - Nilma; Arum Dwi Anjani; Dian Juni Eka Sari (Zona Kebidanan: Program Studi Kebidanan Universitas Batam, 2023)
The vulnerability of young women to anemia occurs due to increased iron needs, excessive menstrual bleeding and lack of balanced nutritional intake (Rati & Jawadagi, 2014). Efforts to increase the hemoglobin level of pregnant women apart from giving Fe tablets, can also be combined with complementary therapies, one of which is by consuming eggs. Objective To provide comprehensive and continuous midwifery care for adolescents, with management of midwifery care in accordance with midwifery service standards. Midwifery care that is applied is the provision of chicken eggs to increase Hb levels in adolescents. Method The type of research used in the preparation of the practice report was a descriptive study conducted at the Tanjung Balai Karimun Health Center in January 2023. Results Evaluation of the care provided related to anemia showed that consumption of chicken eggs helped increase Hb levels in the blood in adolescents. Conclusion SOAP data on midwifery care related to Midwifery Care for Adolescents by implementing the consumption of Dark Chocolate in adolescent midwifery care to relieve menstrual pain